Gender Equality as The Missing Link Towards the African Renaissance. - Koliswa Matebese- Notshulwana; Teboho J. Lebakeng (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
This advocacy paper seeks to problematise the marginalisation, if not total exclusion, of women in one of the major African projects aimed at revitalising and re-awakening the African continent, namely the African renaissance. This marginalisation is not by default but is a result of historical, cultural and social factors that fostered gender inequalities characteristic of African socieities today. Despite the African renaissance being touted as a way to address poverty, instability and social inequalities the contnent is still in a debilitating cycle of crises. Taking cognisant of the above unpalatable situation, the paper reaffirms the enduring and critical contributions of women historically and in the present in various spheres. Thus, it argues that there is an urgent need to engender the African renaissance and to strategically reposition women to be indispensable role players in what is fundamentally their future. This call is premised on the fact that women constitute a critical mass as a majority on the continent hence the need to mainstream them in policy formulation, decision making and implementation so that they also determine the future of the continent. This advocacy paper is methodologically based on existential reality of women on the continent and interactions with women across the board personally and in terms of encounters with their writings. The paper concludes that unless this critical resource is considered, and not overlooked, and Africans inaugurate an epistemic break in the way the re-awakening of the continent is conceptualised, the African renaissance will remain illusive and a pipe dream or mirage.